Low-virulence phylogenetic background of CTX-M-producing Escherichia coli isolated from extraintestinal infections - Andyara L. Paiva; Nilton Lincopan; Ketrin C Silva; Patrícia R Neves; Andrea M Moreno; John A McCulloch; Claudete S Astolfi-Ferreira; Antonio JP Ferreira (Journal of Infection in Developing Countries)
This item has no abstract. Follow the links below to access the full text.